KONSEP KONSUMSI DALAM EKONOMI ISLAM KONTEMPORER VERSI ABDUL MANNAN DAN MONZER KAHF (Abad XIV H/ XV H/ Abad 20 M) - Sandi, Ahmad; Kara, Muslimin; Masse, Rahman Ambo (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2024)
The purpose of this article is to find out and explore the views of Muhammad Abdul Mannan and the views of Monzar Kahf as contemporary Islamic economic thinkers with a focus on consumption. This research is conceptual research using qualitative research methods with literature review. The data used is secondary data, where secondary data is obtained from journal articles, proceedings, conferences, online news and official sites that have relationships or keywords that are appropriate to the topic. From the views of these two contemporary Islamic thinkers, regarding consumption, Muhammad Abdul Mannan emphasizes five principles of consumption, namely: Justice, cleanliness, simplicity, generosity and morality. Meanwhile, Monzer Kahf ties consumption in Islam to three things, namely Islamic rationalism, the concept of falah and the time scale.